Medical male circumcision coverage from 2007 to 2014 in Rakai, Uganda - Kong, Xiangrong (AIDS, 2017)
We assessed medical male circumcision (MMC) scale-up in Rakai Uganda using population-based surveys during 2007–2014. MMC coverage increased from 28.5% to 52.0%. Coverage was initially lower in 15-19-years olds but increased in 2014, was higher in married men and in trading communities, and lowest in the sexually inactive. Coverage did not vary by self-perceived risk of HIV or HIV serostatus. Increasing generalized coverage suggested that MMC became normative, but coverage falls short of WHO/UNAIDS 80% targets, indicating the need for demand generation.